Recent advances in biogas purifying technologies: Process design and economic considerations. (15th February 2023) - Yusuf, Noor; Almomani, Fares
Abstract: Biogas is a promising renewable energy source that is produced from biowaste and can potentially replace conventional energy resources. The economic value of biogas, which is primarily comprised of CH4, CO2, and other impurities (e.g. H2 S, and N2 ) can be increased by upgrading and purification. This study presents the techno-economic feasibility of the cryogenic biogas upgrading process (CBioUP) based on product purities, biomethane selling prices and different refrigeration systems over 25 years of lifetime. The proposed CBioUPs is comprised of compression, refrigeration, and separation sections. Compressed biogas was liquefied in two refrigeration systems (propane pre-cooled mixed refrigerants and optimized cascade technologies) followed by a distillation separation unit. CBioUP proved its flexibility in terms of the number of distillation columns to produce low-grade CH4 (≈94.58 mol%), high-grade CH4 (≈97.13 mol%), and liquid CO2 by-product. The process's robustness to varying biogas feed composition revealed higher CO2 content would necessitate additional duty and/or equipment to enhance separation efficiency, whereas a CH4 content of ≥70% generated biomethane with a purity >99.6 mol% even in a single distillation column. CBioUP demonstrated its suitability for producing different grades of CH4 with a promising net present value (NPV) of $28.3 and $30.9 billion for low/high-grade biomethane.